2018
DOI: 10.3390/w10060806
|View full text |Cite
|
Sign up to set email alerts
|

Water Quality Prediction Model of a Water Diversion Project Based on the Improved Artificial Bee Colony–Backpropagation Neural Network

Abstract: Prediction of water quality which can ensure the water supply and prevent water pollution is essential for a successful water transfer project. In recent years, with the development of artificial intelligence, the backpropagation (BP) neural network has been increasingly applied for the prediction and forecasting field. However, the BP neural network frame cannot satisfy the demand of higher accuracy. In this study, we extracted monitoring data from the water transfer channel of both the water resource and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(28 citation statements)
references
References 8 publications
0
28
0
Order By: Relevance
“…The closer R 2 is to "1", the higher the correlation is. Conversely, the closer R 2 is to "0", the lower the correlation is [45]. As listed in Table 3, the R 2 values of the ABC-BP, PSO-BP, GA-BP, and BP models were 0.983, 0.864, 0.826, and 0.653, respectively.…”
Section: Model Trainingmentioning
confidence: 95%
“…The closer R 2 is to "1", the higher the correlation is. Conversely, the closer R 2 is to "0", the lower the correlation is [45]. As listed in Table 3, the R 2 values of the ABC-BP, PSO-BP, GA-BP, and BP models were 0.983, 0.864, 0.826, and 0.653, respectively.…”
Section: Model Trainingmentioning
confidence: 95%
“…Karaboga proved that artificial bee colony (ABC) algorithms were more precise than GA and PSO [150]. Chen et al [4] proposed an improved method of ABC (IABC) which added the optimal and global optimal solution to the updated formulas. The result indicated that the limitation of the method above was that water quality data needed to obey the normal distribution appropriately.…”
Section: Artificial Neural Network Models For Water Quality Predictionmentioning
confidence: 99%
“…Water quality prediction is one of the purposes of model development and use [2], which aims to achieve appropriate management over a period of time [3]. Water quality prediction is to forecast the variation trend of water quality at a certain time in the future [4]. Accurate water quality prediction plays a crucial role in environmental monitoring, ecosystem sustainability, and human health.…”
Section: Introductionmentioning
confidence: 99%
“…However, this paper does not solve the problem of vanishing gradients due to LSTM. Chen [7] et al proposed a water quality prediction method based on an improved artificial bee colony (IABC) and backpropagation neural network (BPNN). BPNN whose connection weight values between network layers and the threshold of each layer have already been optimised by an IABC algorithm.…”
Section: Introductionmentioning
confidence: 99%